The Ethical Compass in Medical Education. Forging Moral Agents in a Dynamic Healthcare Environment (Revista Iberoamericana de Bioética, 2025)
The text highlights the need to integrate ethics into medical education to train professionals who are not only technically competent, but also morally responsible. It uses the figure of Ulysses in the Odyssey to illustrate the importance of resilience and introspection in times of adversity. It emphasizes that, although scientific and technical advances are crucial, they must be accompanied by solid ethical training to face the challenges of the current health environment. Medical ethics is not only based on theoretical principles, but also on the practice of virtues such as prudence and respect. In addition, the article underlines the importance of a curriculum that includes both formal training and the influence of the ‘hidden curriculum’, i.e. implicit learnings acquired through experience and interaction with mentors and colleagues.
Keywords: ethics; medical education; competence; virtue; values; moral development